Intra‐annual variability of heat wave episodes over the east coast of India. (1st January 2018) - Sandeep, A.; Prasad, V. S.
Abstract : Time‐series of area‐averaged maximum temperature ( T max ) (top panel), representing the intensity of heat wave, and the corresponding T max anomalies are shown in bars (bottom panel), illustrating the intra‐annual variability of heat waves. The dashed black (red) lines represents climatological temperature + 4 (5) °C, respectively. ABSTRACT: India is very prone to heat waves during April–June. The intra‐annual variability of heat wave episodes over the east coast of India has been studied using 16‐year NCMRWF global forecast system (NGFS) retrospective data. The objective of this study is threefold: (1) identification of heat wave episodes over the east coast of India, (2) intra‐annual variability of heat wave episodes, and (3) which physical mechanism(s) is responsible for its occurrence and long‐lasting? A total of ten heat wave episodes (100 hot days) were obtained for the period 2000–2015. The intensity of heat wave is found to be maximum (minimum) for 2015 (2007) episode. The average duration of heat wave episodes was 10 days, with the longest episode lasting for 20 days in the year 2003. Moreover, an average duration of severe heat wave is 3.5 days longer than that of a normal heat wave. The common feature observed in all heat wave cases is the presence of anticyclone in the upper troposphere and associated persistence high. This can cause sinking motion, which leads to surface warming due to adiabatic compression. The lack of soil moisture (SM) induces a positive feedback between the surface and the air above it, which amplifies the sensible heating and thereby increases surface temperature. The prevailed westerly anomalies over the study region which reduce the land–sea breeze result in heat wave. The heat wave episodes exhibit a significant intra‐annual variability. Intensity of heat waves averaged over the east coast of India has shown an increase of 0.06 °C per heat wave. The geopotential height anomaly, vertical velocity, and SM exhibit significant intra‐annual variability between the episodes and become decisive parameters for the maintenance and variability. The correlation coefficient between the maximum temperature and SM is found to be −0.56, indicating the importance of SM regulating the intensity of heat waves.